FAMILY CONFLICT IN E. LOCKHART’S NOVEL WE WERE LIARS - Tri Mauli Dina; Andang Suhendi (Universitas Islam Sumatera Utara, 2019)
This paper discusses the causes of the conflict in the family in E. Lockhart’s novel We Were Liars. There are there causes of the conflict in the family occurred in the novel. They are different social system, different personality, and needs. The method used in analyzing the topic in this thesis is qualitative research method. The theory of the types of the causes of conflict used in this analysis is following Wirawan. The first cause is the different social system. This cause deals with different ethnicity and status which are found in the novel. The second is different personality. This cause is triggered by greed, selfishness, and anger. Those can be found in the novel. Some characters show such personalities. Then, the third is needs. The needs of treasure and inheritance result in conflict in the family in the novel. Thus, it can be found that the conflict appears in the family in the novel due to three main causes; the different social system, the different personality, and the needs.